Outcomes and hospital admissions during long-term support with a HeartMate II. (2nd November 2015) - Rossing, Kasper; Junge, Mette Holme; Sander, Kaare; Olsen, Peter Skov; Hansen, Peter Bo; Boesgaard, Søren; Gustafsson, Finn
Abstract>: Objectives. Continuous-flow left ventricular assist devices like the HeartMate II (HMII) improves survival in severe heart failure but little is known about the incidence and causes of hospitalizations during long-term support which was evaluated in this study. Design. Observational follow-up study comprising all patients who received a HMII at our institution either as bridge-to-transplantation (BTT) or destination therapy (DT). All patients were followed from HMII implantation to transplantation, device explantation, death, or May 2015. Results. The HMII was implanted in 66(44 BTT, 22 DT) patients with a median (range) duration of support since implantation of 329(2–2707) days with 260(2–1080) days in the BTT group and 608(6–2707) days in the DT group. Thirty-day mortality was 12% and one-year survival 76%, comparable for DT and BTT. Among 56 (19 DT and 37 BTT) patients discharged alive with a HMII there were 161 hospital readmissions during a follow-up of 336(37–2682) days corresponding to a hospitalization rate of 1.3(0–19) per patient year and with a length of stay of 5(2–72) days per admission. Most frequent cause of readmission was infections (29%). A history of atrial fibrillation was the only independent factor associated with increased readmission rates. Conclusions: Our single-center study demonstrated encouraging survival following HMII implantation. Hospital readmissions were frequent, mostly of short duration, mainly due to infections and increased in patients with atrial fibrillation.